Neuronal loss of TRPM8 leads to obesity and glucose intolerance in male mice - D. Liskiewicz; Q. Zhang; C.S. Barthem; M. Jastroch; A. Liskiewicz; N. Khajavi; G. Grandl; C. Coupland; M. Kleinert; C. Garcia-Caceres; A. Novikoff; G. Maity; et al. (Elsevier, 2023)
Objective: Mice with global deletion of the transient receptor potential channel melastatin family member 8 (TRPM8) are obese, and treatment of diet-induced obese (DIO) mice with TRPM8 agonists decrease body weight. Whether TRPM8 signaling regulates energy metabolism via central or peripheral effects is unknow. Here we assessed the metabolic phenotype of mice with either Nestin Cre-mediated neuronal loss of TRPM8, or with deletion of TRPM8 in Advillin Cre positive sensory neurons of the peripheral nervous system (PNS). Methods: Nestin Cre- and Advillin Cre-Trpm8 knock-out (KO) mice were metabolically phenotyped under chronic exposure to either chow or high-fat diet (HFD), followed by assessment of energy and glucose metabolism. Results: At room temperature, chow-fed neuronal Trpm8 KO are obese and show decreased energy expenditure when acutely treated with the TRPM8 selective agonist icilin. But body weight of neuronal Trpm8 KO mice is indistinguishable from wildtype controls at thermoneutrality, or when mice are chronically exposed to HFD-feeding. In contrast to previous studies, we show that the TRPM8 agonist icilin has no direct effect on brown adipocytes, but that icilin stimulates energy expenditure, at least in part, via neuronal TRPM8 signaling. We further show that lack of TRPM8 in sensory neurons of the PNS does not lead to a metabolically relevant phenotype. Conclusions: Our data indicate that obesity in TRPM8-deficient mice is centrally mediated and likely originates from alterations in energy expenditure and/or thermal conductance, but does not depend on TRPM8 signaling in brown adipocytes or sensory neurons of the PVN.